2015
DOI: 10.1016/j.ophtha.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Among Methods of Retinopathy Assessment (CAMRA) Study

Abstract: Purpose We compared smartphone fundus photography, nonmydriatic fundus photography, and 7-field mydriatic fundus photography for their abilities to detect and grade diabetic retinopathy (DR). Design This was a prospective, comparative study of 3 photography modalities. Participants Diabetic patients (n = 300) were recruited at the ophthalmology clinic of a tertiary diabetes care center in Chennai, India. Methods Patients underwent photography by all 3 modalities, and photographs were evaluated by 2 retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 31 publications
2
74
0
3
Order By: Relevance
“…Bland-Altman analysis demonstrated an average difference Although diabetic macular edema, for example, can be imaged using this technique (right), it has been reported that insufficient sensitivity is achieved when the technique is integrated into the screening workflow. 34 Left and center panel reproduced with permission from Bastawrous 33 ; right panel reproduced with permission from Ryan et al 34 of -.02 with 95% limits of agreement between -.21 and .16 for vertical cup-to-disc ratio assessment, suggesting good agreement between the lay-operated Peek Retina and the reference standard. 43 Peek Retina preproduction prototypes, shown in Figure 5, are presently being trialled alongside standard digital retinal cameras (Topcon NRW6, Topcon Corp, Tokyo, Japan) in an 18-site DR screening implementation and evaluation in Moshi, Tanzania.…”
Section: Direct Ophthalmoscopymentioning
confidence: 94%
See 1 more Smart Citation
“…Bland-Altman analysis demonstrated an average difference Although diabetic macular edema, for example, can be imaged using this technique (right), it has been reported that insufficient sensitivity is achieved when the technique is integrated into the screening workflow. 34 Left and center panel reproduced with permission from Bastawrous 33 ; right panel reproduced with permission from Ryan et al 34 of -.02 with 95% limits of agreement between -.21 and .16 for vertical cup-to-disc ratio assessment, suggesting good agreement between the lay-operated Peek Retina and the reference standard. 43 Peek Retina preproduction prototypes, shown in Figure 5, are presently being trialled alongside standard digital retinal cameras (Topcon NRW6, Topcon Corp, Tokyo, Japan) in an 18-site DR screening implementation and evaluation in Moshi, Tanzania.…”
Section: Direct Ophthalmoscopymentioning
confidence: 94%
“…34 The authors found the sensitivity of the smartphone images to be 81% and 50% compared to each standard respectively and the specificity to be 94% against each standard. They therefore concluded that 20D lens-assisted smartphone photography lacks sufficient sensitivity for detection of DR.…”
Section: Monocular Indirect Ophthalmoscopymentioning
confidence: 97%
“…However, the non-mydriatic camera was more sensitive at detecting DR than the smartphone. [35] diabEtEs ElEctronic MEdical rEcords Diabetes is a chronic disease requiring lifelong follow-up and monitoring. Unfortunately, levels of glycaemic control have been found to be poor even among patients attending specialised diabetes clinics.…”
Section: Smartphone-based Retinal Photographymentioning
confidence: 99%
“…More straightforward operation of fundus cameras was further improved due to the development of nonydriatic imaging and near-infrared focusing, which increased reproducibility. For example, the Nidek Model AFC-230 (Nidek Inc., Fremont, CA), a nonmydriatic fundus camera with a 45-degree field view, has been demonstrated to be an efficient screening tool for diabetic retinopathy in a clinical trial [11] .…”
Section: Introductionmentioning
confidence: 99%